Pengukuran Konsentrasi Coarse Particle di Ruangan dengan Sistem Kontrol Temperatur Udara - Budianto, Arif; Juniarti, Rosita; Wirawan, Rahadi; Rahayu, Susi (LPPM Universitas Mataram, 2024)
Particulate matter is an air emission that is compossed of particle and liqud dropplet. This suspension is easily measured in several size distributions: ultrafine particle, fine particle, coarse particle, and total suspended particle. Coarse particle is commonly used as a parameter of air quality index. This research aims to measure coarse particle concentrations inside an air-conditioned room. The measurement was conducted using a particulate sensor and a microcontroller for an hour. All measurements were varied into: active and non active room conditions. The results show that human activities and movements in the first variation has higher concentration than the second one. The difference is about 12 Âµg/m3. human activities have a significant role in the submicron particulate distribution inside a room. Air-conditioned room has higher concentration than a common room.